Acceptability of Standard Indian English Morpho-Syntactic Features: An Empirical Study - Mriganka Choudhury (English Teaching and Linguistics Journal (ETLiJ), 2021)
ABSTRACTThe emergence of varieties of English over the years has been the outcome of some prolonged and sustained struggles for their acceptance and linguistic legitimacy. These varieties which include not only Indian, Pakistani, Singaporean English but also American, Australian, New Zealand, Welsh, Scottish and Irish English among others have had to struggle against the perceived superiority of British English to assert their legitimacy even among their people (Choudhury, 2018). We have a well-documented record of the struggles for linguistic independence of American English. Studies conducted among the users of different varieties of English have, in recent times, shown greater acceptability of their own varieties of English. However, the acceptability is not universal and a large number of users of the language still regard their own varieties to be “low” in comparison to the native varieties. Baumgardner states that had similar studies on American English been done in the nineteenth century, a similar disparity of views would have been found (Baumgardner, 1996, p. 262). Although Indian English has gained legitimacy as a variety with its distinct lexical, morpho-syntactic and discourse features, its acceptability among the users of the language needs to be ascertained. The purpose of the study is to examine the acceptability of Standard Indian English usage among the people very closely associated with the English language through an analysis of subject response to a questionnaire comprising Standard Indian English morpho-syntactic items.